Improve the Motivation of Learning and Learning Outcomes Passing Down volleyball Through Cooperative Learning Model - Wibisono, Rezeki; Kartiko, Dwi Cahyo; Hartoto, Setiyo (Universitas Negeri Semarang, 2018)
The purpose of this research is to know the improvement of learning motivation and the result of passing down learning in volleyball game through applying cooperative learning method Student Teams Achievement Divisions (STAD) in class V SD Raden Patah. The type of research used in this study is Classroom Action Research (CAR). Working procedures taken in this PTK is a cycle, which consists of four stages, namely the planning (planning), the stage of action (action), observation (observation) and reflection stage (reflection). The result of the research shows that in cycle 1 students’ learning motivation and learning result of passing under volleyball as many as 20 students (65%) have achieved minimum mastery criteria (KKM) and the remaining 11 students (35%) have not reached KKM. In Cycle II the students’ learning motivation and learning outcomes of passing under the volleyball were 27 students (87%) had achieved KKM scores and 4 students (13%) had not reached KKM scores. Based on the results of the study of passing out learning under volleyball by using STAD type cooperative learning model can increase the interest and motivation of learning to passing learning process under volleyball so as to achieve KKM value. Improvement of learning outcomes of students of grade V SD Raden Patah Surabaya can be seen from each aspect during cycle I and cycle II. Psychomotor value in cycle I reaching KKM as much as 65%, while in cycle II reach 87%. Results of cognitive assessment during the first cycle as much as 74% and increased in cycle II to 94%. Based on the above analysis, it can be concluded that through cooperative learning model type STAD can improve learning motivation and learning outcomes passing under volleyball on subjects PJOK in grade V students Semester II SD Raden Patah Surabaya Lesson Year 2017/2018.